(untitled) (Journal of the College of Basic Education, 2023)
Fire was one of the discoveries by chance that man worked to use in Developing intentional inventions. It was a miracle that God Almighty created for man (1). Since he discovered her, he saw her violent, killing, destroying, and annihilating. The fearsome, which is darkness, and the authors of the speech said: (Indeed, God, the Mighty and Sublime, has combined movement and heat in Hell. dryness, gentleness, and light, and it acts on each of these forms through what it does with the other.